Two new species of Amazonian Lecythidaceae - Prance, Ghillean Tolmie; Anderson, Anthony B. (Brittonia, 1976)
Two new species of Lecythidaceae from Brazilian Amazonia are described and illustrated: Cariniana penduliflora and Couratari atrovinosa. Details of the pollination of Couratari atrovinosa are given, the principal pollinator being a Euglossine bee, Eulaema meriana Oliv. © 1976, The New York Botanical Garden. All rights reserved.